Tutor Support in the Ungraded School of the North - Neustroev, Nikolai Dmitrievich (2020)
The study is aimed at providing scientific substantiation of the relevance of the tutors’ activities and at describing the educational experimental program implemented at the Department of Primary Education of the North-Eastern Federal University concerning primary education and tutoring in the general ungraded and nomadic schools of the North. Research methods include: study and analysis of scientific literary sources, including those considering the problems of education in Yakutia; analysis of the tutor support organization for school education in the North; and simulation of a tutor support model in a nomadic school. Teacher training experience was obtained in introducing a new combined profile in the bachelor’s program “Primary Education and Tutoring in the General Ungraded and Nomadic Schools of the North”. The article describes a model for the formation of ethno-educational competence in primary school teachers, ethno-pedagogization of the educational process and the national civic identity as a condition for the successful implementation of the tasks of the new standard for primary school, and deals with the content and stages of the formation of bachelors’ ethno-educational competencies in future primary school teachers as exemplified by Ammosov North-Eastern Federal University.